Testing to Identify Submaximal Effort: Lifting to a Perceived 50% Effort vs. an Assigned Submaximal Load. Issue 8 (10th August 2022) - Swift, Marcie C.; Townsend, Robert; Edwards, Douglas; Loudon, Janice K.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Swift, MC, Townsend, R, Edwards, D, and Loudon, J. Testing to identify submaximal effort: Lifting to a perceived 50% effort vs. an assigned submaximal load. J Strength Cond Res 36(8): 2115–2120, 2022—The ability to accurately measure effort during postinjury functional testing allows for the validation of displayed physical limitations by injured workers. The Cross-Reference Testing System (XRTS) has been developed to identify submaximal efforts through distraction-based dynamic material handling testing. The XRTS material handling assessment compares dynamic lifts of weights in a crate and lifts using a lever arm device. The purpose of this study was to determine whether subjects lifting an assigned submaximal load influence test results compared with subjects lifting to but not exceeding a 50% perceived effort. Subjects in group A ( n = 35) were assigned the condition to attempt to lift to but not exceed a randomly assigned weight value for both the crate lift and XRTS at 3 lifting heights. Subjects in group B ( n = 32) were asked to lift to but not exceed 37.5 lb from the same 3 lifting heights. The reproducibility of effort was measured with current validity criteria for distraction-based material handling testing. Using the percent difference values, a 2 × 3 (group, lifting height) analysis of variance (ANOVA) was performed to test the hypothesis. The alpha level was set at 0.05. The mean percent change between comparative lifts was 31.13%, 95% CI (22.51–39.75) for group A and 29.26% 95% CI (21.91–36.61) for group B. The 2 × 3 ANOVA demonstrated no significant difference ( p = 0.751) between groups. The results indicate attempting to lift to a perceived 50% effort was not significantly different from attempting to lift to but not exceed an assigned submaximal load.